Analysis of the digital strategy of the Gastronomy Museum and its influence on visitor satisfaction levels in pandemic times - Pino-Apablaza, Fernando (2024)
The research sought to determine significant differences between the levels of satisfaction in two independent samples, both made up of groups of visitors to the Museum of Gastronomy in its virtual and face-to-face modality. In addition, with the help of a rubric, the level of use of digital technologies used in the museum was analyzed. The methodology was descriptive and explanatory with quasi-experimental design exposfacto. Visitor satisfaction data were collected through two questionnaires with reliability levels of 0,817 and 0,859 respectively. The hypothesis test was performed with the Student's T test. The P-value obtained was lower than the value of Alpha, which was considered 0,05. Therefore, significant differences were evidenced between the means of both groups of museum visitors, being the group of virtual visitors, the one that obtained higher levels of satisfaction. It is concluded that the virtual version of the museum in times of pandemic generated more satisfactory experiences than the face-to-face experience.